Peningkatan Manajemen Usaha Pada Pembenihan Ikan ‘Kolam As Syifa’ Cindai Alus - Emmy Sri Mahreda; Rina Mustika; Irma Febrianty; Lindawati Lindawati; Pajar Pardian (Universitas Lambung Mangkurat, 2021)
AbstractThe purpose of the community partnership program activities: improving business management through bookkeeping and report training (logbooks, cash books, inventory, and balance sheets) and increase knowledge to assess business viability through profit analysis training, Cost-Revenue Ratio, Payment Period, and Break-Even Point. The methods applied are 1. the stage of the situation and condition of the partners, 2. the stage of preparation of all materials and materials for training activities, 3. the stage of counseling and management training (training on preparing and presenting reports), analytical training according to final needs, and 4. the stage of evaluation. Community partnership program activities to improve business management for hatcheries at the As Syifa Pond Business provide increased understanding and skills of fish breeders about professional business management through increasing ability in compiling simple financial reports/bookkeeping and in analyzing business financially. This increase in understanding and skills is not only felt for current operations but also business development in the future.Keywords: management, business, bookkeeping, feasibility, As Syifa Abstrak Tujuan kegiatan PKM adalah: perbaikan manajemen usaha melalui pelatihan penyusunan pembukuan dan laporan keuangan (log book, buku kas, buku persediaan dan neraca) dan meningkatkan pengetahuan untuk menilai kelayakan usaha melalui pelatihan menganalisis keuntungan, Revenue Cost Ratio, Payback Period dan Break Even Point. Metode kegiatan yang diterapkan adalah: 1. tahap analisis situasi dan kondisi mitra, 2. tahap persiapan semua bahan dan materi untuk kegiatan pelatihan, 3. tahap penyuluhan dan pelatihan manajemen usaha (pelatihan pembuatan dan penyajian laporan keuangan), pelatihan menganalisis kelayakan usaha secara finasial, dan 4. tahap evaluasi PKM. Kegiatan PKM perbaikan manajemen usaha terhadap pembenih ikan pada Usaha Kolam As Syifa memberikan peningkatan pemahaman dan keterampilan pembenih ikan tentang manajemen usaha yang profesional melalui peningkatan kemampuan dalam menyusun laporan keuangan/pembukuan sederhana dan dalam menganalisis kelayakan usaha secara finansial. Peningkatan pemahaman dan keterampilan ini bukan hanya dirasakan untuk operasional saat ini, tetapi juga untuk pengembangan usaha di masa depan.Kata kunci: manajemen, usaha, pembukuan, kelayakan, As Syifa